Composing and connecting devices in animal telemetry network - Krishna, Ashwin (Kansas State University, 2016)
As the Internet of Things (IoT) continues to grow, the need for services that span multiple application domains will continue to increase to realise the numerous possibilities enabled by IoT. Today, however, heterogeneity among devices leads to interoperability issues while building a system of systems and often give rise to closed ecosystems. The issues with interoperability are driven by the inability of devices and apps from different vendors to communicate with each other. The interoperability problem forces the users to stick to one particular vendor, leading to vendor lock-in. To achieve interoperability, the users have to do the heavy lifting (at times impossible) of connecting heterogeneous devices. As we slowly move towards system-of-systems and IoT, there is a real need to support heterogeneity and interoperability. A recent effort in Santos Lab developed Medical Device Coordination Framework (MDCF), which was a step to address these issues in the space of human medical systems. Subsequently, we have been wondering if a similar solution can be employed in the area of animal science. In this effort, by borrowing observations from MDCF and knowledge from on-field experience, we have created a demonstration showcasing how a combination of precise component descriptions (via DSL) and communication patterns can be used in software development and deployment to overcome barriers due to heterogeneity, interoperability and to enable an open ecosystem of apps and devices in the space of animal telemetry.
Keywords: Internet of Things; Animal Telemetry; Automation; Distributed Systems; Sensor Network